Utilizando ferramentas da genética forense para investigar a origem dos indivíduos do canário-da-terra (Sicalis flaveola) mantidos em cativeiro - Sandoval-Arias, Shirleny (2020)
Wildlife protection is a global priority issue. International treaties, laws, national entities and organizations fight for the conservation of biodiversity and protection of wildlife, generating environmental awareness mainly against the illegal trade of wild animals. Illegal trade is the third most common illegal activity, second only to arms and narcotics trafficking. Brazil is responsible for about 10 to 15% of the global value of wild animal trafficking of all kind of species however birds are the most affected, being the Psittaciformes and Passeriformes (saffron finch, bird of interest for the present study) the groups most commonly apprehended by environmental authorities. According to IBAMA, saffron finch (Sicalis flaveola) is one of the ten species of birds most illegally trafficked in the country and a recent study has shown that this is also the most hunted species in the state of São Paulo, despite of being reproduced in numerous breeding sites in the state. In addition, at least four species of the same genus are recognized in Brazil, and three are present in the state of São Paulo, therefore, confirmation of the species in the breeding site is important. In this scenario, an important question stands out: are the individuals of the species Sicalis flaveola kept in commercial breeding sites, really the result of reproduction in captivity? To answer this question we will use genetic tools to confirm the species and to analyze parental relationships. We will carry out species delimitation analyzes, using the mitochondrial marker COI and the distance (DNA Barcoding) and coalescence (bPTP and GMYC) approaches to verify whether the collected samples are of the species Sicalis flaveola and confirm their validation for this taxon. Subsequently, the transferability of 26 microsatellite locos described for different species of Passerines will be evaluated to determine their usefulness to analyze parental relations of individuals of Sicalis flaveola sampled at breeding sites in actions carried out by the Military Environmental Police. Using parental estimators based on the probability of identity by offspring, it is possible to confirm the genetic link between the sampled birds. In the end, the project has the aim to produce a tool to determine if the birds are actually the result of breeding in the breeding site, as possibly claimed by the breeders or would be a captured free-living bird, contributing to the detection of possible violations of current laws.